PERBANDINGAN KINERJA KEUANGAN PEMERINTAH KABUPATEN/KOTA DI PROVINSI JAWA BARAT TAHUN 2009-2013 - Dwi Asri, Jatnika (Jurnal Riset Akuntansi dan Keuangan, 2016)
Abstract. This study aims to analyze the comparison of financial performance as well as analyze whether there are differences in financial performance between districts/cities in West Java Province during 2009-2013. The research used the descriptive method with quantitative data analysis technique of financial ratios as well as T test and Mann-Whitney test. The results showed that city government has a higher level of independence ratio than the district. The district effectiveness ratio is very effective with an average of 120.06%. T and Mann-Whitney test results showed no difference between effectiveness ratio, while independence ratio showed the difference.Keyword: Financial performance; Effectiveness Ratio; Independence RatioÂ Abstrak.Penelitian ini bertujuan untuk menganalisis perbandingan kinerja keuangan serta menganalisis apakah terdapat perbedaan kinerja keuangan antara kabupaten/kota di Provinsi Jawa Barat selama 2009-2013. Penelitian menggunakan metode deskriptif dengan teknik analisis data kuantitatif rasio keuangan serta uji T dan uji Mann-Whitney. Hasil penelitian menunjukkan pemerintah kota mempunyai tingkat rasio kemandirian lebih tinggi dibandingkan kabupaten. Rasio efektivitas kabupaten/kota sangat efektif dengan rata-rata 120.06%. Hasil uji T dan Mann-Whitney menunjukkan tidak terdapat perbedaan antara rasio efektivitas, sedangkan rasio kemandirian menunjukkan perbedaan.Kata Kunci: Kinerja Keuangan; Rasio Efektivitas; Rasio Kemandirian